E-Business Issues, Challenges and Opportunities for SMEs: Driving Competitiveness - Maria Manuela Cruz-Cunha
Designing digital marketplaces for competitive advantage.- E-commerce systems for software agents: Challenges and opportunities.- Enhancing the preparedness of SMEs fir e-Business opportunities by collaborative networks.- E-learning for SMEs: challenges, potential and impact.- 21st Century learning opportunities for SME success: maximizing technology tools and lofelong learning for innovation and impact.- Open innovation: opportunities and challenges for SMEs.- Organizational readiness/preparedness.- Digital marketplaces as a viable model for SME networking.- What is new with organization of e-business: organizational viewpoint of the relationships.- Knowledge supply for SME networks: application cases and selected technical approaches.- SME as a service.- Reflecting on new business models for SMEs through technological application: cases of e.business in Brasil.- E-Health business model prototyping by incremental design.- Specifications for a website audit tool for small business.- An approach to efficient waste management for SMEs via RBVOs.- Retail 2.0: the coming up of a new era for retail business in the 21st century.- A unfied view of enablers, barriers, and readiness of small to medium enterprises for e-business adption.- Issues influencing electronic commerce activities of SMEs: a study of Turkish automotive supplier industry.- Constrain associated to E-business evolution.- An integrative framework on the psychological variable explaning the consumers' use of e-commerce-based recommendation systems.- Fairness in virtual teams: a construct of e-organizational justice.- Open innovation in SMEs: from closed peripheries to networked paradigm.